Fundamental Issues in the Simulation of Human Behavior: A Case in the Strategy of Behavioral Science - Mitroff, Ian I. (Management Science, 1969)
Every scientific study has its own unique case history. Unfortunately, most scientific papers present a greatly distorted and static image of the true history and sociology of a research project. This paper represents an attempt to report on selected aspects of the actual growth and development of a simulation project, especially as that process affected the development of a novel method for validating simulation models. The paper also represents a philosophical analysis of the concept of simulation, especially as that analysis formed an integral part of the study's development. One of the paper's main theses is that the teleology or purpose behind the construction of a simulation model is an ever present task-master guiding and influencing all the phases of a model's construction and validation. A general thesis is that a researcher's philosophy of science is as characteristic of him (i.e., his psychology) as it is of the phenomena he typically studies. The implications of these theses are illustrated in terms of the simulation of the engineering design behavior of a practicing mechanical engineer.